The Principle of Justice in the Restriction of Rights Against Unvaccinated Groups (Kanun: Jurnal Undang-undang Malaysia, 2022)
Unvaccinated groups are exempted from any legal action under the Prevention and Control of Infectious Diseases Act 1988 or any other written law. Basically, everyone has the right to make a decision on themselves. The same goes for the individual’s right to choose to be vaccinated or otherwise. As citizens, we are bound by the law of the country and it becomes an obligation to implement it. However, the choice to not be vaccinated will result in various restrictions imposed on the said groups. These restrictions are made according to the law and are in the public interest to protect the people. Thus, these groups claim that they were not treated equally to those who chose to be vaccinated. It should be noted that the law in Malaysia is not limited to the “naturalist” theory which is concerned with morality only, but is also positive in nature, which is concerned with compliance with the law that is enacted, even if there is an element of injustice towards some parties. This article will answer the question of whether the restrictions in the social activities and movements of unvaccinated individuals are justified based on the theory of justice. This article is based on a qualitative study which is analyzing the principles of justice in the restriction of rights against the unvaccinated according to the views of jurisprudent figures critically. Based on the findings, restrictions against unvaccinated groups are permissible. Therefore, this study is important in order to explain that discrimination against the unvaccinated groups is fair.Keywords: Vaccine, anti-vaccine, justice, restriction, discrimination, equalityFull text: PDF